2003
DOI: 10.1364/ao.42.002730
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hadamard transformers by use of multimode interference optical waveguides

Abstract: We propose a synthesis method of optical Hadamard transformer using multimode interference (MMI) couplers. By using the signal transfer matrix of 2 x 2, 4 x 4, and 8 x 8 MMI couplers, we show that sum and difference units of input signals can be synthesized. An interchange unit of two signals can also be synthesized. One synthesis method of Hadamard transformers is a combination of only 2 x 2 units, and the other is a combination of N x N(N > or = 4) units as well as 2 x 2 units. The design examples of operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…When the width has about 1μm error, which is about 3% of the total width, the mode extinction ratio degrades to 20dB. This is in agreement with the analysis in [16], which indicated that the width error has a stronger impact on the MMI coupler performance and it can be proportionally related to the length error by a factor of 2 [16]. The operation wavelength range can be evaluated by relating the wavelength deviation to the length deviation [16].…”
Section: Numerical Results and Discussionsupporting
confidence: 79%
“…When the width has about 1μm error, which is about 3% of the total width, the mode extinction ratio degrades to 20dB. This is in agreement with the analysis in [16], which indicated that the width error has a stronger impact on the MMI coupler performance and it can be proportionally related to the length error by a factor of 2 [16]. The operation wavelength range can be evaluated by relating the wavelength deviation to the length deviation [16].…”
Section: Numerical Results and Discussionsupporting
confidence: 79%
“…In [7], the Hadamard transform based on MMI couplers has been proposed. By controlling the phase of the input signals at the entrance of the MMI coupler, and cascading the MMI couplers, 2×2 and 8×8 Hadamard transformers have been designed.…”
Section: Photonic Signal Transformsmentioning
confidence: 99%
“…It will now be shown how such elements can be formed from MMI structures. We start with a restricted interference (RI) based 2×2 MMI coupler [1] that has a transfer matrix [7] …”
Section: Discrete Fourier Transformmentioning
confidence: 99%
“…As such, in the last few decades and especially in recent years, there has been an increasing worldwide trend on the research and development of basic optical signal processing devices that can emulate the fundamental functionalities of the much more mature electronic counterparts but with a much higher processing speed/bandwidth. In this direction, a number of basic analog optical signal processors have been reported, which include the temporal optical differentiators [4][7], temporal optical integrators [6]− [9], ODFTs [1], [10][13], [29][32], optical inverse DFTs [1], [12], optical Hilbert transformers [14][16], optical discrete sine transformers [17], optical discrete cosine transformers [17], [18], optical discrete Hartley transformer [18], optical Hadamard transformers [13], [19], and optical discrete wavelet transformers [20].…”
Section: Introductionmentioning
confidence: 99%